2020
DOI: 10.3390/rs12111808
|View full text |Cite
|
Sign up to set email alerts
|

Digital Aerial Photogrammetry (DAP) and Airborne Laser Scanning (ALS) as Sources of Information about Tree Height: Comparisons of the Accuracy of Remote Sensing Methods for Tree Height Estimation

Abstract: The rapid developments in the field of digital aerial photogrammetry (DAP) in recent years have increased interest in the application of DAP data for extracting three-dimensional (3D) models of forest canopies. This technology, however, still requires further investigation to confirm its reliability in estimating forest attributes in complex forest conditions. The main purpose of this study was to evaluate the accuracy of tree height estimation based on a crown height model (CHM) generated from the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 79 publications
3
28
0
1
Order By: Relevance
“…Our research result was that coupling oblique photos and nadir photos can effectively improve the vertical coordinate accuracy of the point cloud. However, it is worth noting that under the premise of not using GCP, the height coordinate error provided by the scheme with nadir-photos-only reached 10.8 m (Figure 11), which is quite different from the results of other researchers [35][36][37]. The specific reason for this result is not clear, but it may be related to the camera calibration result or ground type, which can be further explored in future research.…”
Section: Three-dimensional Reconstructionmentioning
confidence: 64%
“…Our research result was that coupling oblique photos and nadir photos can effectively improve the vertical coordinate accuracy of the point cloud. However, it is worth noting that under the premise of not using GCP, the height coordinate error provided by the scheme with nadir-photos-only reached 10.8 m (Figure 11), which is quite different from the results of other researchers [35][36][37]. The specific reason for this result is not clear, but it may be related to the camera calibration result or ground type, which can be further explored in future research.…”
Section: Three-dimensional Reconstructionmentioning
confidence: 64%
“…A variety of comparable studies on the performance of LiDAR and USP point clouds for forest attribute parameters have been conducted [16] including diverse forest environments such as complex boreal forest types, complex coastal forest [18], and subtropical planted forests [19]. Most studies have concluded that LiDAR provides higher accuracy for modeling and predicting forest attributes than stereo photogrammetry data [20][21][22]. However, few studies have analyzed the performance of USP on temperate coniferous plantations in mountainous area.…”
Section: Introductionmentioning
confidence: 99%
“…The most common products of aerial image processing are vector maps, orthophoto maps, digital terrain models (DTM), and digital surface models (DSM) [20][21][22]. In recent years, digital aerial cameras and appropriate software development have provided sensors with higher resolution, allowing the Earth's surface to be captured with detail-level improvement at the same flight height, respectively reducing the necessary number of images and thus flight time and cost of imaging [23]. The minimizing of fieldwork time, rapidity of photogrammetric data collection and processing, and high detail and accuracy of the terrain models generated by modern software currently take aerial photogrammetry forward as an exciting alternative in terms of quality and efficiency in comparison with terrestrial geodetic methods [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, from the available methods for performing the required measurements, the method of aerial photogrammetry has been chosen as likely the most appropriate way to fulfil the purpose of measurement. The advantages of this method consist of the very short time for measurement, fast and automated data processing procedures, sufficient precision, the non-contact method of measuring, and the minimized working time in the factory [3,18,23].…”
Section: Introductionmentioning
confidence: 99%